1995
DOI: 10.1007/bf00202265
|View full text |Cite
|
Sign up to set email alerts
|

Complement C1q and C3 mRNA expression in the frontal cortex of Alzheimer's patients

Abstract: The levels and cellular localization of mRNA for complement C1q and C3 were examined by RNA gel blot and nonradioactive in situ hybridization in the frontal cortex of patients with Alzheimer's disease (AD) and age-matched controls. We found that the hybridization signal for C1q mRNA was markedly increased (approx. 3.5-fold) in the frontal cortex of AD patients compared to that in age-matched controls. In contrast to previous reports we also found that the levels of C3 mRNA, although well expressed, did not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…However, both neurons and glia have been reported to express complement proteins, leaving unclear which cell types mediate specific aspects of the complement response (Fischer et al, 1995;Shen et al, 1997;Walker et al, 1998;Lue et al, 2001). Using in situ hybridization and immunofluorescence staining, we show here that under physiological conditions, C3 is primarily expressed in astrocytes where its expression is further upregulated in APP/PS1 (Tg) and APP/TTA mice.…”
Section: Discussionmentioning
confidence: 60%
“…However, both neurons and glia have been reported to express complement proteins, leaving unclear which cell types mediate specific aspects of the complement response (Fischer et al, 1995;Shen et al, 1997;Walker et al, 1998;Lue et al, 2001). Using in situ hybridization and immunofluorescence staining, we show here that under physiological conditions, C3 is primarily expressed in astrocytes where its expression is further upregulated in APP/PS1 (Tg) and APP/TTA mice.…”
Section: Discussionmentioning
confidence: 60%
“…6,8,9,20,21 Cells in the central nervous system (CNS) are capable of synthesizing a complete set of complement components and upregulating this production in response to injury. [22][23][24][25] Additionally, it has been demonstrated that complement activation has deleterious proinflammatory effects in other CNS processes, such as Alzheimer disease. 26 -30 Finally, neurons in vitro are highly susceptible to complement-mediated lysis, leading to the hypothesis that complement can cause neuronal death through membrane attack complex (MAC) deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is evidence that in the course of cerebrovascular disease and Alzheimer's disease, serum proteins like Ig, fibrinogen, and complement factors are deposited in the brain parenchyma (41). Although there is accumulating evidence for enhanced cerebral biosynthesis of C1q in Alzheimer's disease brain, based on Northern blot, RT-PCR, and Western blot results, the issue of neuronal vs nonneuronal biosynthesis of C1q in normal human brains and in Alzheimer's disease brains is still controversial (2,5,7,8,41,42). Likewise, in experimental studies of different types of inflammatory and neurodegenerative brain lesions, the neuronal vs nonneuronal biosynthesis of C1q is a matter of controversy (21, 22, 24 -27).…”
Section: Discussionmentioning
confidence: 99%